Israf and Tabzir in Tafsir Al-Misbah: The Understanding of Pidie Jaya Community Leaders and Its Implications for Consumption in Aceh - Fuadi, Fuadi; Zulkarnain, Zulkarnain; Boihaqi, Boihaqi; Ibrahim, Muhammad Syahrial Razali (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2024)
Modernization has shifted Acehnese society from simplicity to consumerism. In Islam, excessive consumption is classified as israf (overspending on permissible matters) and tabzir (wasting wealth on non-beneficial purposes). Quraish Shihab’s Tafsir Al-Misbah highlights their role in social inequality and spiritual degradation. This study employs a qualitative descriptive-interpretative approach, utilizing library research and semi-structured interviews with three community leaders in Pidie Jaya. Data were analyzed thematically and interpretatively, comparing respondents’ views with Tafsir Al-Misbah. The findings indicate that the respondents’ understanding aligns with Quraish Shihab’s exegesis, although they place greater emphasis on economic aspects over spiritual dimensions. This awareness helps prevent a status-driven consumer culture in Aceh, confirming that balanced consumption is integral to the principle of hifzul mal (preserving wealth) in Islam. However, strong social norms promote excessive spending, necessitating educational strategies through religious institutions, formal education, and social media to cultivate ethical consumption habits in line with Islamic values.